Virtual reality for acrophobia: Evaluating the usability of a commercial VRBox - Valero Aguayo, Luis (Revista Española de Comunicación en Salud, 2023)
Introduction: The virtual reality (VR) has already been shown to be effective for phobias such as flying, agoraphobia, driving, insects, and rodents, etc., but it requires creating the virtual worlds adapted to the individual. Objectives: The aim was to access the usability, satisfaction and difficulties encountered by consultants with an affordable VR system (VRBox and a quality mobile phone) with 360º images freely available on the Internet for acrophobia. Method: 47 people aged 18-69 years, 21 of whom were female (45%), participated in this study. Users were exposed to 10 of 360-degree videos, in a VRBox headset that included a mobile phone. Questionnaires on anxiety, specific height phobia, usability, and satisfaction with the experience and equipment were administered. Results: Usability scores were high (M = 73.51 out of 100 points) and anxiety levels were low (M = 2.50 out of 10 points). No significant differences were found between men and women; those with previous VR experience rated it better; and those with vertigo or dizziness rate it lower and with more anxiety. Conclusion: The VR system for acrophobia is accepted and well appreciated by most users, although the technological system should be adapted to the individual, especially if discomfort arises when using it.